1987
DOI: 10.2134/jeq1987.00472425001600040026x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Production throughout the Year from Fertilized and Manured Maize Fields

Abstract: Two field sites on a loam soil were established to monitor N20 concentration in the soil atmosphere and rate of emission from the soil surface. The sites were cropped to maize (Zea mays L.) and managed at two high-N levels (181 or 237 kg N ha-~). Both sites received 168 kg N ha -~ as feedlot cattle (Bos taurus) manure (preplant-incorporated) and 13 kg N ha -~ as NH4NO~ fertilizer in the row at planting. One site (Site B) received additional soil-incorporated N (56 kg N -~) asure a. Fluctuations in N20 emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(36 citation statements)
references
References 16 publications
3
30
2
1
Order By: Relevance
“…Based on our measurements, we cannot be certain which of the mechanisms suggested by Cates and Keeney (1987) were involved in the high N 2 O fluxes at spring thaw: rapid nitrification-denitrification at the soil surface, and/or release of N 2 O accumulated below the frozen layer in the soil profile. But it is apparent that the absence of high N 2 O fluxes for alfalfa and grass plots at spring thaw was linked to the low nitrate levels observed (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Based on our measurements, we cannot be certain which of the mechanisms suggested by Cates and Keeney (1987) were involved in the high N 2 O fluxes at spring thaw: rapid nitrification-denitrification at the soil surface, and/or release of N 2 O accumulated below the frozen layer in the soil profile. But it is apparent that the absence of high N 2 O fluxes for alfalfa and grass plots at spring thaw was linked to the low nitrate levels observed (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Other studies have observed high emissions at spring thaw as affected by manure or fertilizer addition in the previous year (Goodroad et al 1984;Cates and Keeney 1987). But the relative importance of these emissions in relation to fluxes due to fertilizer or manure application during the growing season has not been well established before.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has illustrated effects of crop rotation, tillage, irrigation, crop residues, soil conditions (temperature, water status, pH, salt content, and available C), manure, and fertilizer use on emissions of N 2 O and other greenhouse gases from maize-based systems in the north-central United States (119,121,(124)(125)(126)(127)(128)(129). However, most of these estimates were obtained from small experimental field plots, which may not be representative of production-scale fields.…”
Section: Soil Quality Nitrogen Requirements and Greenhouse Gas Emismentioning
confidence: 99%
“…A diurnal variation can also exist, primarily associated with temperature variations (Denmead et al, 1979;Conrad et al, 1983;Slemer et al, 1984). Seasonal fluctuations also occur due to 'bursts'of substrate availability following perturbations such as dryingiwetting and freezelthaw events (Cates & Keeney, 1987;Parton et al, 1988;Christensen & Tiedje, 1990).…”
Section: Coz Emissionsmentioning
confidence: 99%